Gourmet and health-promoting specialty oils - Kamal-Eldin, Afaf; Moreau, Robert (AOCS Monograph Series in Oilseeds, 2009)
The third volume in the AOCS PRESS MONOGRAPH SERIES ON OILSEEDS is a unique blend of information focusing on edible oils. These oils contain either unique flavor components that have lead to their being considered "gourmet oils," or contain unique health-promoting chemical components. Each chapter covers processing, edible and non-edible applications, lipids, health benefits, and more related to each type of oil